2002
DOI: 10.1046/j.1526-0968.2002.00419.x
|View full text |Cite
|
Sign up to set email alerts
|

Leukocytapheresis Using a Leukocyte Removal Filter

Abstract: Leukocytapheresis (LCAP) long has been investigated with a leukocyte removal filter for the treatment of various kinds of autoimmune related and inflammatory diseases such as rheumatoid arthritis, inflammatory bowel disease, multiple sclerosis, and so on. A lot of patients with such diseases have been reported to respond to LCAP. Asahi Medical Co. has developed the leukocyte removal filter Cellsorba and an extracorporeal treatment unit Plasauto LC so that the LCAP technique can be performed easily with a high … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0
1

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 10 publications
2
40
0
1
Order By: Relevance
“…This is similar to the previous studies in patients with rheumatoid arthritis and ulcerative colitis and healthy volunteers (23)(24)(25). It has been reported that the peripheral blood platelets were removed while passing through the column (26).…”
Section: Discussionsupporting
confidence: 90%
“…This is similar to the previous studies in patients with rheumatoid arthritis and ulcerative colitis and healthy volunteers (23)(24)(25). It has been reported that the peripheral blood platelets were removed while passing through the column (26).…”
Section: Discussionsupporting
confidence: 90%
“…These leukocytes include granulocytes, lymphocytes and monocytes. Almost 100% of granulocytes and monocytes and 60% of lymphocytes are removed by removal filter [24,25] . It has been reported that 73.3% of steroid-refractory patients with UC enter remission after LCAP [26] .…”
Section: Discussionmentioning
confidence: 99%
“…4 3 How does leukocytapheresis contribute to suppressing the pathology in the hemodynamics of colitogenic memory CD4 + T cells described in the previous section? The principal methods of leukapheresis used clinically are granulocyte and monocyte adsorption apheresis (GCAP; Adacolumn), 44 which chiefly removes granulocytes and monocytes, and leukocytapheresis (LCAP; Cellsorba), 45 which removes lymphocytes, monocytes and granulocytes as a whole. We recently reported that LCAP therapy selectively removed CD4 + CD45RO + CD62L -T EM cells, which have a similar phenotype of murine colitogenic memory CD4 + T EM cells without affecting CD4 + CD25 + Foxp3 + T R cells, which suppress immunity.…”
Section: + T Cells For the Treatment Of Ibdmentioning
confidence: 99%